SPASMOGENIC NONCHOLINERGIC ACTIVITY OF A DIGESTIVE GLAND HOMOGENATE OF THE AMPHIBIAN SNAIL POMACEA-LINEATA SPIX-1827 - Craveiro, JPM; Mendes, E. G. (Associação Brasileira de Divulgação Científica (ABRADIC), 1991)
The digestive gland of Pomacea lineata, a prosobranch gastropod mollusc inhabiting both fresh water and land, does not contain cholinomimetic compounds as do the glands of species of Aplysia, marine opisthobranch gastropods, in which both acetylcholine and urocanylcholine are present. The only pharmacological action detected for the digestive gland of Pomacea was spasmogenic activity of a crude homogenate containing 0.1 g tissue equivalents on the snail's own esophagus bathed in 10 ml of a physiological solution prepared on the basis of the animal's hemolymph composition. The spamodic activity was not blocked by atropine, bromlysergic acid diethylamide or anthazoline.
Keywords: Pomacea lineata; MOLLUSK DIGESTIVE GLAND; CHOLINOMIMETIC COMPOUNDS; SPASMOGENIC ACTIVITY